Threshold Genres: A 10-Year Exploration of a Medical Writer's Development and Social Apprenticeship Through the Patient SOAP Note. (July 2022) - Driscoll, Dana Lynn; Yacoub, Omar
While writing is a critical part of the medical profession, longitudinal studies exploring the social apprenticeship and genre knowledge development of medical practitioners are almost nonexistent. Through interviews and writing samples, this article traces a 10-year journey of one writer's engagement with the Patient SOAP note, following his experiences from the first year of his undergraduate education to the end of medical school. Drawing upon theories of social apprenticeship and the RIME framework (reporter, interpreter, mediator, educator) from the field of medicine, we offer an in-depth case study of our focal participant's growing medical expertise as he masters the Patient SOAP note. Through this in-depth analysis, we argue that the SOAP note functions as a "threshold genre" to assist entry into the medical profession. We conclude by offering additional evidence about the role that key threshold genres play in the development of professional expertise and offer implications for genre theory.